Ulama dalam Dinamika Sosial dan Budaya Masyarakat Aceh di Awal Abad Kedua Puluh Satu - Aslam Nur (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2011)
The Acheh Ulama who live in the early of 21st century do not play their esential role in multifunctional frame and polimorfict leadership pattern as the characteristic of the Achehness Ulama did in the past. Yet, now they perform one role only (monofunctional) in monomorfic leadership system. Nevertheless, this research found that Ulama’s leadership is still needed by the Acehness community.